Legal Protection Of Cybercrime Crimes From Ransomware Attacks And Evaluation Of The Cyber Security And Resilience Bill 2025 In Indonesia'S Defense - Sulubara, Seri Mughni; Tasril, Virdyra; Nurkhalisah, Nurkhalisah (Universitas Muhammadiyah Sumatera Utara, 2025)
The legal safeguarding against ransomware cybercrime is found in multiple regulations. Indonesia possesses various legal frameworks to combat cybercrime, such as the Electronic Information and Transaction Law (UU ITE), the Personal Data Protection Law (UU PDP), and the Criminal Code (KUHP). Ransomware is a type of harmful software. Ransomware locks a user’s data within a computer network, preventing an individual or business from accessing their information. Hackers subsequently extort the victim for a ransom to allow the data owner to regain access to the data. Usually, the payment of the ransom is conducted through cryptocurrency to ensure it remains untraceable. The research methodology, or a means to reach the objectives outlined in the study, employs a qualitative descriptive approach grounded in juridical or normative legal research. This method aims to assess how well the 2025 cyber security and resilience bill can enhance Indonesia's digital defense. The ITE law establishes a legal framework for prosecuting cyber offenders, including ransomware, but it lacks detailed regulations regarding the terminology and methods of ransomware. This creates difficulties in law enforcement, particularly in demonstrating criminal aspects and gathering electronic evidence. Law number 27 of 2022 regarding personal data protection (PDP LAW) establishes a robust legal structure to safeguard personal data from abuse, particularly in relation to ransomware offenses that frequently involve data theft and manipulation. Article 368 of the criminal code concerning conventional extortion can be utilized in ransomware situations, despite not explicitly addressing the digital format. Article 368 of the criminal code addresses the crime of conventional extortion applicable to ransomware incidents, even if it doesn't specifically cover the digital format. The cybersecurity and resilience bill of 2025 aims to enhance Indonesia's cyber defense, emphasizing the protection of cyberspace and the national digital ecosystem. In this regard, the cybersecurity and resilience bill (RUU KKS) 2025 represents a vital measure for the government to bolster national cyber defense. This legislation is intended to outline the responsibilities of various parties in ensuring cybersecurity, set incident reporting requirements, and impose severe penalties for breaches, including prison terms of up to 20 years and fines reaching Rp20 billion.